ONLINE TESTING OF LANGUAGE SKILLS - FEDIC, Dusan (Trends in education, 2010)
The article deals with the implementation of ICT into language skills online system at the FMST SUT. The article characterizes a web application "Testing system", which will be used for students testing before their compulsory language preparation at the FMST. The article describes the instructions for the use from user and administrator positions.
Keywords: ICT; online testing; language skills.